Barriers and Facilitators of Research in Pediatric Sports Medicine Practitioners: A Survey of the PRiSM Society - Dai Sugimoto; Michael Del Bel; Lauren Butler (North American Sports Medicine Institute, 2022)
# Background Barriers and facilitators to research in sports medicine (SM) by physicians and allied health (AH) professions such as physical therapists and athletic trainers are understudied. The purpose of this research was to examine and compare research barriers, facilitators, and other research related facets including interests, comfort, knowledge, and resources among SM physicians and AH practitioners. # Study Design Cross-sectional survey # Methods The survey was sent to Pediatric Research in Sports Medicine (PRiSM) members. The survey was designed to ask respondents to identify their top barrier and facilitator to conducting research. Research interest (binary), self-rated comfort reading research articles (0-100 scale), self-rated knowledge conducting research independently (0-100 scale), and available research resources were evaluated. Descriptive statistics, chi-square, and t-tests were used to compare the responses between SM physicians and AH practitioners. The value of p<0.05 was set as a statistically significant criterion. # Results The response rate was 35.7% (N=100). For both SM physicians and AH practitioners, the greatest research barrier was a lack of time. However, the leading research facilitators differed in the two professions. The top research facilitator for SM physicians was availability of research personnel, while availability of research mentoring was selected as a prime facilitator by AH practitioners. There were no differences in research interest between SM physicians (87.0%) and AH practitioners (95.5%, p=0.267). However, self-rated comfort reading research articles was higher in SM physicians (75.6±20.6) than AH practitioners (60.6±28.3, p=0.018). There were no differences in self-rated knowledge conducting research independently between SM physicians (70.2±18.6) and AH practitioners (63.4±24.6, p=0.163). # Conclusion Lack of time was the top research barrier for both SM physicians and AH practitioners. Regarding research facilitators, having available time was the main facilitator for SM physicians while availability of mentoring was the leading facilitator in AH practitioners. # Level of Evidence: 3